Clinical and Molecular Characterization of Ataxia with Oculomotor Apraxia Patients In Saudi Arabia - Alkhairallah Thamer S; Khalil Dania S; Al Sharif Latifa J; Shinwari Jameela M; Bohlega Saeed A; Al Tassan Nada A (BMC, 2011)
Abstract Background Autosomal recessive ataxias represent a group of clinically overlapping disorders. These include ataxia with oculomotor apraxia type1 (AOA1), ataxia with oculomotor apraxia type 2 (AOA2) and ataxia-telangiectasia-like disease (ATLD). Patients are mainly characterized by cerebellar ataxia and oculomotor apraxia. Although these forms are not quite distinctive phenotypically, different genes have been linked to these disorders. Mutations in the APTX gene were reported in AOA1 patients, mutations in SETX gene were reported in patients with AOA2 and mutations in MRE11 were identified in ATLD patients. In the present study we describe in detail the clinical features and results of genetic analysis of 9 patients from 4 Saudi families with ataxia and oculomotor apraxia. Methods This study was conducted in the period between 2005-2010 to clinically and molecularly characterize patients with AOA phenotype. Comprehensive sequencing of all coding exons of previously reported genes related to this disorder (APTX, SETX and MRE11). Results A novel nonsense truncating mutation c.6859 C > T, R2287X in SETX gene was identified in patients from one family with AOA2. The previously reported missense mutation W210C in MRE11 gene was identified in two families with autosomal recessive ataxia and oculomotor apraxia. Conclusion Mutations in APTX , SETX and MRE11 are common in patients with autosomal recessive ataxia and oculomotor apraxia. The results of the comprehensive screening of these genes in 4 Saudi families identified mutations in SETX and MRE11 genes but failed to identify mutations in APTX gene.